SCORE2 Assessment in the Calculation of Cardiovascular Risk in Patients with Rheumatoid Arthritis - Iván Ferraz-Amaro; Alfonso Corrales; Belén Atienza-Mateo; Nuria Vegas-Revenga; Diana Prieto-Peña; Julio Sánchez-Martín; Cristina Almeida; Juan Carlos Quevedo-Abeledo; Ricardo Blanco; Miguel Á. González-Gay (Diagnostics, 2021)
Patients with rheumatoid arthritis (RA) are at increased risk for cardiovascular disease (CVD). Risk chart algorithms, such as the Systematic Coronary Risk Assessment (SCORE), often underestimate the risk of CVD in patients with RA. In this sense, the use of noninvasive tools, such as the carotid ultrasound, has made it possible to identify RA patients at high risk of CVD who had subclinical atherosclerosis disease and who had been included in the low or moderate CVD risk categories when the SCORE risk tables were applied. The 2003 SCORE calculator was recently updated to a new prediction model: SCORE2. This new algorithm improves the identification of individuals from the general population at high risk of developing CVD in Europe. Our objective was to compare the predictive capacity between the original SCORE and the new SCORE2 to identify RA patients with subclinical atherosclerosis and, consequently, high risk of CVD. 1168 non-diabetic patients with RA and age > 40 years were recruited. Subclinical atherosclerosis was searched for by carotid ultrasound. The presence of carotid plaque and the carotid intima media wall thickness (cIMT) were evaluated. SCORE and SCORE2 were also calculated. The relationships of SCORE and SCORE2 to each other and to the presence of subclinical carotid atherosclerosis were studied. The correlation between SCORE and SCORE2 was found to be high in patients with RA (Spearman’s Rho = 0.961, p < 0.001). Both SCORE (Spearman’s Rho = 0.524) and SCORE2 (Spearman’s Rho = 0.521) were similarly correlated with cIMT (p = 0.92). Likewise, both calculators showed significant and comparable discriminations for the presence of carotid plaque: SCORE AUC 0.781 (95%CI 0.755–0.807) and SCORE2 AUC 0.774 (95%CI 0.748–0.801). Using SCORE, 80% and 20% of the patients were in the low or moderate and high or very high CVD risk categories, respectively. However, when the same categories were evaluated using SCORE2, the percentages were different (58% and 42%, respectively). Consequently, the number of RA patients included in the high or very high CVD risk categories was significantly higher with SCORE2 compared to the original SCORE. (p < 0.001). In conclusion, although predictive capacity for the presence of carotid plaque is equivalent between SCORE and SCORE2, SCORE2 identifies a significantly higher proportion of patients with RA who are at high or very high risk of CVD.